Physico-chemical and Biological Investigations of Ocimum Basilicum L. Cultivated in Algeria - Merzouki, Soraya; Boukeria, Sabah; Louafi, Fadila; Alma, Mohemet Hakki; Erenler, Ramazan; Yildiz, Ilyes; Boulkroune, Mina; Mouats, Chabane (Current Chemical Biology, 2024)
IntroductionThis study aims to explore biologically active substances from natural sources, such as the Ocimum basilicum L. plant, for potential medicines.MethodsThe LC-MS/MS analysis reveals that the majority of compounds in the aerial portion of this plant have Hesperidin and Vanillic acid, which are used in treating blood vessel fragility and neurological diseases like Alzheimer's and Parkinson's. The study conducted a qualitative phytochemical screening of the hydromethanolic plant extract, revealing different secondary metabolites. Quantitative studies were conducted to determine the quantities of polyphenols, flavonoids, tannins, and alkaloids in the extract.ResultsOur investigations also assessed the antioxidant activity of the hydromethanolic plant extract using DPPH-free radical scavenging and cyclic voltammetry, providing insights into its potential to combat oxidative stress.ConclusionFinally, the anticoagulant activity of the hydromethanolic plant extract was examined through Quick and Cephaline Kaolin time coagulation exploration tests, providing insights into its impact on coagulation pathways.
Keywords: Ocimum basilicum L.